An online questionnaire study about factors affecting first aid knowledge of citizens in Hong Kong - Leung, Shek Ming; Eagle Li, Kin Chun; Leung, Pui Yan; Lo, Hau Wan; Li, Sin Man; Lui, Yuen Ching; Leung, Shuk Yi; Leung, Ka Wing (International Journal Of Community Medicine And Public Health, 2022)
Background: The study aimed to identify the factors associated with first aid knowledge among Hong Kong citizens. Methods: This was a questionnaire study that collected demographic data and assessed first aid knowledge. Multiple regressions were used to identify factors associated with first aid knowledge and participation in first aid course. Results: Better knowledge was associated with participation in first aid course (beta=1.53, 95% confidence interval: 0.98 to 2.08), experience of performing first aid (beta=0.88, 95%CI: 0.19 to 1.57), medical-related course (beta=0.89, 95%CI: 0.21 to 1.58), males (beta=0.67, 95%CI: 0.17 to 1.17) and less years past after first aid course completion (beta=-0.08, 95%CI: -0.15 to 0) (n=230). Respondents with medical-related education background (OR=2.33, 95%CI: 1.03 to 5.27) had more participation in first aid course. Conclusions: First aid course participation was the most important factor associated with knowledge. Regular refresher courses and promotion towards citizens without medical-related education background were recommended.